PRKX down-regulates TAK1/IRF7 signaling in the antiviral innate immunity of black carp Mylopharyngodon piceus - Yang, Xiao; Ai, Yue; Chen, Liang; Wang, Chanyuan; Liu, Ji; Zhang, Jie; Li, Jun; Wu, Hui; Xiao, Jun; Chang, Mingxian; Feng, Hao (Frontiers in Immunology, 2023)
TGF-β-activated kinase-1 (TAK1), tightly related to innate immunity, is phosphorylated and activated by X-linked protein kinase (PRKX) in human and mammals, which belongs to the c-AMP-dependent protein kinase family. However, the relationship between PRKX and TAK1 remains unknown in teleost. Our previous study has revealed for the first time in vertebrates that black carp TAK1 (bcTAK1) associated with bcIRF7 and up-regulated bcIRF7-mediated IFN signaling. In this study, the role of PRKX homologue of black carp (Mylopharyngodon piceus) (bcPRKX) in bcTAK1/IFN signaling has been explored. Overexpression of bcPRKX suppressed the transcription of interferon promoters, but enhanced the transcription of NF-κB promoter. Mylopharyngodon piceus kidney (MPK) cells transfected with shRNA targeting bcPRKX presented the enhanced antiviral activity against spring viremia of carp virus (SVCV), in which the mRNA levels of the antiviral proteins were increased, including Mx1, Viperin and PKR. Overexpressed bcPRKX dampened bcTAK1/bcIRF7/IFN signaling in the reporter assay and plaque assay. The interaction between bcTAK1 and bcPRKX has been identified by the immunofluorescence (IF) staining and co-immunoprecipitation (co-IP) assay. Interestingly, the protein level of bcTAK1 was decreased when co-expressed with bcPRKX, which was recovered by the chloroquine but not MG132. Thus, we conclude that bcPRKX inhibits bcTAK1/bcIRF7/IFN signaling during the innate immune activation by targeting bcTAK1 and triggers lysosome-dependent degradation of bcTAK1.